(untitled) (Biological Sciences - PJSIR, 2001)
Tenekil-M (polychlorinated petroleum hydrocarbon) an indigenous compound, Furadon (carbofuran) and Rugby (Cadusafos) were applied for controlling Helicotylenchus multicinctus, H. indicus, Hoplolaimus columbus, Pratylenchus coJJeae, P zeae and Tylenchorhynchus annulatus in banana. After the application of Tenekil-M, population of nematodes was suppressed as compared to carbofuran and Cadusafos. Tenekil-M was significantly effective than Furadon and Rugby. Average weight of the harvested bunches of banana was greater in Tenekil-M treated plants than those treated with Furadon and Rugby and the control.